The Use of 2D Plastic Grating for Surface Profile and Dimension Manufacture Product Measurements by Using NDT Moiré Technique - P., Retno Wigajatri; Andiani, Dini (Makara Journal of Technology, 2002)
The Use of 2D Plastic Grating for Surface Profile and Dimension Manufacture Product Measurements by Using NDT Moiré Technique. Research of measuring the shape and dimension of object using the moiré technique have been done. Measurement have been made by observing the moiré space as a result of interaction between grating and its shadow casted on the object’s surface caused by the projector lamp with CCD camera. The acquired data was further processed by way of off-line. By successive phase shifts that is π/2, π dan 3π/2 towards the table tennis ball at the distance of 48 cm from the light source and CCD camera, with the distance between CCD Camera and light source 13,5 cm and grating space 0,5 mm. It was obtained that convex shape can be identified by resolution of 0,24 mm. It was also shown that the biggest difference between the results of using moiré technique and the use of CMM contact measurements (Coordinate Measuring Machine) was 0,3 mm